Pattern of utilization of health insurance in two districts of South Karnataka - Shet, Nagaraj; Qadiri, Ghulam Jeelani; Saldanha, Sunita; Kanalli S., Gayathri; Sharma, Prajna (International Journal Of Community Medicine And Public Health, 2019)
Background: Health insurance is a widely recognized and preferable mechanism to finance the health care expenditure of the individuals. It is an important mechanism in the modern world to save the individuals from the huge health shock but only a small percentage of people even from educated higher income groups are covered under any health insurance policy. This study was undertaken to know the pattern of health insurance utilization in Uttar Kannada and Udupi districts of Karnataka. Methods: A descriptive study was conducted among 550 household of Uttar Kannada and Udupi districts. Household were selected using multistage sampling technique. Results: Of the 550 study participants, 348 (63.27%) were aware and also subscribed for any type of the health insurance and of these only 89 (25.57%) utilized them. 190 (34.55%) had availed Rashtriya Swastya Bima Yojana, 42 (7.64%) for Yashasvini, 6 (1.09%) forESI, 12 (2.18%) for Sampoorna Suraksha and 15 (27.27%) had private insurances. Reasons for not availing health insurances other than being unaware were complicated process 85 (42.08%) and provides only partial coverage 49 (24.26%). The main reasons for not using the health insurance were non availability of empaneled hospital 84 (74.34%), disease not being under the scope of scheme 60 (23.17%) and 32 (12.36%) were unaware about the process of availing. Conclusions: Health insurances being are the best way to help people reduce their financial burden has to be made aware and the drawbacks have to be addressed.